Language learning strategies research in English as foreign language contexts: A systematic literature review - Marenco Domínguez, José Miguel; Marín Juanías, José (Journal of Education and Learning (EduLearn), 2024)
The specific processes, techniques, and actions that learners take to facilitate their language learning have been widely explored under the concept of language learning strategies (LLS); however, more exploration is needed about recent investigations in this area, as calls for new theorization of strategies research have emerged. This systematic literature review aimed at exploring the prevailing research methodologies and educational settings appertaining to LLS in English as foreign language (EFL) contexts. The study analyzed 42 articles published from 2017 to 2023 in journals in the field of social sciences in the Scopus and ERIC databases. The findings show how non-intervention quantitative approaches are predominant in LLS research, occasionally accompanied by qualitative data collection methods. Accordingly, most research has favored descriptive and correlational designs, identifying the relationships between the use of strategies and variables such as language proficiency, demographic aspects, motivation, and self-regulation. Grounded on the revision of existing evidence, this article advises future strategy-based research to focus on primary and secondary levels of education, strategy instruction, cultural aspects, and qualitative research designs.